2019
DOI: 10.12659/msm.915450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum Sealing Drainage Combined with Ilizarov Bone Transport Technique in the Treatment of Tibial Traumatic Osteomyelitis

Abstract: BackgroundThe aim of this study was to analyze the efficacy of vacuum sealing drainage combined with Ilizarov bone transport technique in the treatment of tibial traumatic osteomyelitis and risk factors for postoperative pin infection.Material/MethodsWe enrolled 78 patients with tibial traumatic osteomyelitis admitted at the First People’s Hospital of Kashgar from January 2015 to September 2017 and treated with vacuum sealing drainage combined with Ilizarov bone transport technique.ResultsAfter combined treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The number of reinfections in the successful eradication group with NPWT was not significantly lower compared to patients who remained with an ongoing infection ( p = 0.0764), indicating that initially deemed successful treatment with NPWT had no benefit in regards to recurrence rates compared to unsuccessful eradicated infections. Yikemu et al (2019, n = 78) measured infection recurrence as main outcome and reported the second highest infection recurrence in 24.4% as pin tract infection in the course of treatment of traumatic tibial osteomyelitis [ 35 ] with Ilizarov bone transport. There is no description on how pin tract infection was diagnosed, whether it was a pin tract infection only or whether it was an expression of a more extensive FRI recurrence or neither how it was resolved.…”
Section: Resultsmentioning
confidence: 99%
“…The number of reinfections in the successful eradication group with NPWT was not significantly lower compared to patients who remained with an ongoing infection ( p = 0.0764), indicating that initially deemed successful treatment with NPWT had no benefit in regards to recurrence rates compared to unsuccessful eradicated infections. Yikemu et al (2019, n = 78) measured infection recurrence as main outcome and reported the second highest infection recurrence in 24.4% as pin tract infection in the course of treatment of traumatic tibial osteomyelitis [ 35 ] with Ilizarov bone transport. There is no description on how pin tract infection was diagnosed, whether it was a pin tract infection only or whether it was an expression of a more extensive FRI recurrence or neither how it was resolved.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical doctors urgently need to find an effective treatment with obvious efficacy in older patients with infectious bone nonunion after open tibial fracture [8]. Operative surgery is the main clinical treatment of infectious bone nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically, the tibia is the most common site for chronic osteomyelitis to occur [7,12], partially because of its poor blood supply (especially inferior third of tibia), inadequate coverage in the medial surface, higher risk of injuries, and of course, the inappropriate surgical managements. C-M Type III chronic tibial osteomyelitis as a less severe type has not yet received much attention as C-M type IV and thus, is not frequently illustrated by a single study.…”
Section: Introductionmentioning
confidence: 99%